Validity and reliability of the Diagnostic Adaptive Behaviour Scale. (9th November 2015) - Tassé, M. J.; Schalock, R. L.; Balboni, G.; Spreat, S.; Navas, P.
Abstract: Background: The Diagnostic Adaptive Behaviour Scale (DABS) is a new standardised adaptive behaviour measure that provides information for evaluating limitations in adaptive behaviour for the purpose of determining a diagnosis of intellectual disability. This article presents validity evidence and reliability data for the DABS. Method: Validity evidence was based on comparing DABS scores with scores obtained on the Vineland Adaptive Behaviour Scale, second edition. The stability of the test scores was measured using a test and retest, and inter‐rater reliability was assessed by computing the inter‐respondent concordance. Results: The DABS convergent validity coefficients ranged from 0.70 to 0.84, while the test–retest reliability coefficients ranged from 0.78 to 0.95, and the inter‐rater concordance as measured by intraclass correlation coefficients ranged from 0.61 to 0.87. Conclusions: All obtained validity and reliability indicators were strong and comparable with the validity and reliability coefficients of the most commonly used adaptive behaviour instruments. These results and the advantages of the DABS for clinician and researcher use are discussed.